N-Acetyl-2-hydroxy-N'-[methoxy(1-methylindol-2-yl)methyl]benzohydrazide - Yehye, W.A.; Rahman, N.A.; Ariffin, A.; Ng, Seik Weng (International Union of Crystallography, 2008)
In the crystal structure of the title Schiff-base, C(20)H(21)N(3)O(4), the amino group forms an N-H⋯O hydrogen bond to the acetyl group of an adjacent mol-ecule, forming a zigzag chain. The 2-hydr-oxy group is inter-nally hydrogen bonded to the amido group though an O-H⋯O hydrogen bond.